Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I would like some help finding the critical points of $f(x,y)=x^2+xy+y^2+\frac{1}{x}+\frac{1}{y}$. I tried solving $f_x=0, f_y=0$ (where $f_x, f_y$ are the partial derivatives) but the resulting equation is very complex. The exercise has a hint: think of $f_x-f_y$ and $f_x+f_y$. However, I can't see where to use it.


share|cite|improve this question
$f_x$ and $f_y$ are both zero if and only if $f_x+f_y$ and $f_x-f_y$ are both zero. – Rahul Apr 11 '12 at 2:06
Yeah, I know this much. I haven't figured out how to get anything out of the resulting set of equations, however. Maybe I'm missing something really simple, but I just can't see it. – ro44 Apr 11 '12 at 2:09
up vote 2 down vote accepted

After doing some computations I found the following (lets hope I didn't make any mistakes). You need to solve the equations

$$f_x = 2x + y - \frac{1}{x^2} = 0 \quad f_y = 2y + x -\frac{1}{y^2} = 0$$

therefore after subtracting and adding them as in the hint we get

$$\begin{align} f_x - f_y &= x - y - \frac{1}{x^2} + \frac{1}{y^2} = 0 \\ f_x + f_y &= 3x + 3y -\frac{1}{x^2} - \frac{1}{y^2} = 0 \end{align} $$

but you can factor them a little bit to get

$$ \begin{align} f_x - f_y &= x - y + \frac{x^2 - y^2}{x^2 y^2} = (x - y) \left ( 1 + \frac{x+ y}{x^2 y^2}\right ) = 0\\ f_x + f_y &= 3(x + y) -\frac{x^2 + y^2}{x^2 y^2} = 0 \end{align} $$

Now from the first equation you get two conditions, either $x = y$ or $x+y = -x^2 y^2$.

If $x = y$ you can go back to your first equation for $f_x$ and substitute to get

$$2x + x - \frac{1}{x^2} = 0 \implies 3x = \frac{1}{x^2} \implies x = \frac{1}{\sqrt[3]{3}}$$

and then you get the critical point $\left ( \dfrac{1}{\sqrt[3]{3}}, \dfrac{1}{\sqrt[3]{3}} \right )$

Now if instead $x + y = -x^2 y^2$ then if you substitute into the equation $f_x + f_y = 0$ we get the following

$$ 3(-x^2 y^2) - \frac{x^2 + y^2}{x^2 y^2} = 0 \implies 3x^4 y^4 + x^2 + y^2 = 0 \implies x = y = 0 $$

But this is actually one of the points where the partial derivatives or even your original function are not defined.

share|cite|improve this answer
Thank you! This is a good answer. – ro44 Apr 11 '12 at 2:30
@ro44 I'm glad I could help. – Adrián Barquero Apr 11 '12 at 2:38

Here $f_{x}=2x+y-\frac{1}{x^{2}}$ and $f_{y}=2y+x-\frac{1}{y^{2}}$ For critical point $$f_{x}=0,\ f_{y}=0$$ $$2x+y-\frac{1}{x^{2}}=0\ ,\ 2y+x-\frac{1}{y^{2}}=0$$ $$2x^{3}+x^{2}y-1=0\ ,\ 2y^{3}+xy^{2}-1=0$$ Substracting this two equations we get, $$ 2(x^{3}-y^{3})+xy(x-y)=0$$ $$ 2(x-y)(x^{2}+xy+y^{2})+xy(x-y)=0$$ $$(x-y)(2x^{2}+2xy+2y^{2}+xy)=0$$ $$x-y=0\ \Rightarrow x=y$$ Put $x=y$ in $2x^{2}+2xy+2y^{2}+xy=0$,we get, $$ 2x^{2}+2x^{2}+2x^{2}+x^{2}=0\ \Rightarrow x=0 $$ Also $y=0$ \ $\therefore (0,0)$ is a critical point.

share|cite|improve this answer
However $(0,0)$ is not in the domain of the function. You don't need both factors to be $0$ for the product to be $0$, just one. – Ross Millikan Apr 11 '12 at 2:04
You can see $(0,0)$ is a critical point much faster by showing you can't plug it in to either $f_x$ or $f_y$. Also, why are you plugging $x=y$ into $2x^2+2xy+2y^2+xy$? How do you know $2x^2 + 2xy + y^2 + xy (= 2x^2 + 3xy + y^2)$ doesn't have any other solutions? – Jason DeVito Apr 11 '12 at 2:04
@ro44: When he subtracts the two equations he gets $f_x-f_y$ and the result factors as shown. You can show that the second factor is never $0$ except at the excluded $(0,0)$ Then you can take $x=y$ and follow Changwei Zhou to get to his answer. – Ross Millikan Apr 11 '12 at 2:17
@RossMillikan: Yeah, but I get the feeling that's not how the hint is supposed to be used. I'm aware of how to show that $(0,0)$ is the only possible solution but in this course we haven't been taught (or are expected to use) stuff like that, so it's not very satisfying. – ro44 Apr 11 '12 at 2:28

You should solve $f_{x}=0,f_{y}=0$ and we have $2x+y-1/x^{2}=0,2y+x-1/y^{2}=0$. They are just $2x^{3}+x^{2}y-1=0, 2y^{3}+y^{2}x-1=0$. Consider symmetric solutions $(a,a)$ we have $$2a^{3}+a^{3}-1=0\leftrightarrow a^{3}=\frac{1}{3}\leftrightarrow x=y=3^{-\frac{1}{3}}$$

For the non-symmetric case, Solve $2x^{2}+2y^{2}+3xy=0$ implies no real solutions other than $x=y=0$, as the determinant is $9y^{2}-4*2*2y^{2}=-7y^{2}<0$ for $y\not=0$.

This ignores the original point $(0,0)$, which is not defined.

share|cite|improve this answer
You haven't justified the claim that all solutions will be symmetric. – Ross Millikan Apr 11 '12 at 2:07
@RossMillikan: thanks, now justified. – Kerry Apr 11 '12 at 2:15
@ChangweiZhou: Thanks for your answer. It's satisfying, but I'd still like to know how the hint about $f_x +/- f_y$ is supposed to be used. – ro44 Apr 11 '12 at 2:22

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.